Geology, petrography and geochemistry of Archean Tonalitic and Trondhjemitic Associations from Vila Jussara, Carajás Province, Pará - Silva, Alice Cunha da; Dall’Agnol, Roberto; Guimarães, Fabriciana Vieira; Oliveira, Davis Carvalho de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The Archean granitoids exposed near Vila Jussara, in the Transition Subdomain of the Carajás Province are diversified and include the São Carlos Tonalite and Colorado Trondhjemite, named in this work. Both are marked by strong recrystallization, mainly of quartz and plagioclase. The São Carlos Tonalite (~2.93 Ga) is formed mainly by hornblende-biotite tonalite, with NE-SW to N-S-trending foliation. Compared to the Colorado Trondhjemite, it is depleted in silica and enriched in the oxides of the mafic minerals constituents, has low fractionation of heavy Rare Earth Elements (REE) and discrete to absent Eu anomalies. Its characteristics are distinct from those of typical Archean TTG suites and differ also of the Rio Maria Sanukitoid Suite. The Colorado Trondhjemite (2.87 Ga) is composed of epidote-bearing biotite trondhjemites with subordinate tonalites and rare granodiorites (TTG), with steeply-dipping foliation trending E-W to NW-SE, locally N-S. The Colorado trondhjemite geochemical characteristics are consistent with those of Archean TTG suites. It show pronounced HREE fractionation with high (La/Yb)N and two types of REE patterns, one with discrete negative to nearly absent Eu anomalies, and a second one with strong positive Eu anomalies, in most cases, accompanied by a slight decrease in LREE.
Keywords: Carajás Province; Transition Subdomain; Archean; TTG; Tonalite